PERSIAPAN DINAS PARIWISATA DAERAH TINGKAT II SLEMAN DALAM MENYAMBUT PARIWISATA 2005 DAN OTONOMI DAERAH - Larasati, Sri (Sekolah Tinggi Pariwisata AMPTA, 2004)
In the next 2005 RIPPNAS and WTO report that either foreign or domestic tourist are still coming to Indonesia, even move than 8,4 to 10 millions in the end of 2010. The declaration of municipal outhority written in UU No. 22, 1999 conduct Yogyakarta tourism development, especially Sleman district. This research is done not only to know how far Sleman as the whole prepares in future, but found that goverment has already developed tourism sector as well, such like putting down in RIPPDA, without neglecting the national, regional and economics life. Tourism's growing supported by natural, human resources and another sides involve such as culture and business.